The Influence of Product Quality and Consumer Dissatisfaction on Brand Switching Behavior of Marcks Loose Face Powder in Banjarmasin City - Puput Heranika; M. Hasanur Arifin; Hairudinor; Setio Utomo (Magister Administrasi Bisnis ULM, 2025)
This Study aims to determine the effect of Product Quality and Consumer Dissatisfaction on Brand Switching Behavior on Marcks Loose Face Powder in Banjarmasin City. This research uses a quantitative approach. The location of this research was chosen in Banjarmasin City as many as 100 respondents, with data collection using a questionnaire and data analysis using multiple linear regression analysis assisted by IBM SPSS Statistic Version 29. The results of this study prove that Product Quality has a positive and significant effect on Brand Switching Behavior at a moderate level. Consumer Dissatisfaction has a positive and significant effect on Brand Switching Behavior on Marcks Loose Face Powder in Banjarmasin City at a moderate level. And Product Quality and Consumer Dissatisfaction have a positive and significant effect on Brand Switching Behavior on Marcks Loose Face Powder in Banjarmasin City at a strong level